Analysis of efficiency of use of formers for gas concrete with various physical-mechanical and structural characteristics - Gots, V.; Palchik, P.; Palchik, S.; Sanakoev, O. (Ways to Improve Construction Efficiency, 2020)
The development of the market of gas-forming agents takes place in a market economy amid increasing demands on the quality, safety, environmental friendliness and cost-effectiveness of their use. The main blowing agent used at cellular concrete production facilities is pigmented aluminum powders and aluminum pastes. The article provides a comparative description of various types of blowing agents in accordance with specific production conditions. The quality of cellular concrete products largely depends on the reactivity of the used aluminum and on how much it corresponds to the production process, depending on the reactivity of the raw materials. A very important parameter is the stability of the technical characteristics of aluminum pastes over time. This characteristic is very important for ensuring the storage of the paste, its safety during transportation and storage in the warehouse. Depending on the required structure of aerated concrete, coarser or finer powder is used in production. The higher the average density of the product, the coarser the powder should be used. If necessary, you can make powder with any time the start of the reaction of gas formation. The stability of the technological process for the production of cellular concrete products and, as a consequence, the minimization of the amount of substandard products depend to a large extent on the reactivity of the used aluminum and on how much it corresponds to the production process depending on the reactivity of the raw materials. The reactivity of aluminum powder depends on the particle size of aluminum, the structural characteristics of its surface and the properties of the protective film. During the experimental studies, a study was made of the characteristics of aluminum powder of the Ukrainian manufacturer PAP-1 and aluminum paste ALBApor308B (Romania). Based on the analysis of the influence of the considered technical characteristics of aluminum pastes on the course of the technological process and the complex of technical and environmental factors (the cost of the paste, the effectiveness of its use, environmental factors), preference is given to aluminum paste made in Romania by «Alba» company